ASEAN’s Contributions to Attain Peace on The Dynamic of Rohingya Ethic Issue - Fauziyah Aulia Rishanti; Puguh Santoso; Anang Puji Utama (Research Synergy Foundation, 2022)
Humanitarian violence have become a key issue in conflicts that occur, domestically and internationally. This research focuses on how crimes against humanity have occurred in Myanmar, especially in Rakhine-Rohingnya. Furthermore, this study explains how ASEAN’s contribution in urging to resolving the Rohingya ethnic dispute in Myanmar. Moreover, the role of ASEAN in protecting refugees relate to the lost citizenship rights. This study uses deductive explanations and qualitative methods, collecting information through secondary data and interviews with reliable parties.